FACTORS INFLUENCING THE FARMERS’ BEHAVIORAL INTENTIONS OF FARMER CARDS IN SUMENEP REGENCY - Laras Nur Fitriani; Darsono Darsono; Umi Barokah (Agric, 2022)
Many factors cause the issue of fertilizer subsidies. One of them is about the implemented system has not been running optimally. The Farmer Card is an innovation to obtain subsidized fertilizers. The innovation has many obstacles, including the lack of awareness and knowledge of farmers’ human resources (HR) in understanding the innovations’ usefulness. The study’s objective was to determine the factors influencing the acceptance of the Farmer Card based on the Technology Readiness and Acceptance Model (TRAM). Primary data were gained from the farmers by taking a simple random sampling method using the Hair formula for as many as 115 farmers using Farmer Card in Kabupaten Sumenep. The data were analyzed using the quantitative descriptive method through the Partial Least Square (PLS) technique. The study’s objective was to determine the effect of optimism, innovativeness, discomfort, insecurity, perceived usefulness, and perceived ease of use on behavioral intention to use in technology readiness with a p-value of 0.000 (<0.05). The test results show that the variables of optimism (H1 and H2), discomfort (H5), perceived usefulness (H9), and perceived ease of use (H10) have a significant effect on behavioral intention to use Farmer Card. Testing the effect of innovativeness (H3 and H4), discomfort (H6), and insecurity (H7 and H8) showed a p-value of 0.091; 0.259; 0.127; 0.853; 0.385 (> 0.05) means that it has no significance. For the Farmer Card program to be successful, it is recommended to enhance cooperation further and shared views among the farmers and stakeholders.